VD_FINDINFO HC / 2022 / 425 vom 19. Mai 2022 - VD Tribunal cantonal (2022)
EFFET SUSPENSIF, DROIT DE DÉTERMINER LE LIEU DE RÉSIDENCE, OBLIGATION D'ENTRETIEN, DOMICILE COMMUN | 315 al. 4 let. b CPC (CH), 315 al. 5 CPC (CH)